ETNOMATEMATIKA PADA AKTIVITAS PETANI JERUK DI KECAMATAN PESANGGARAN BANYUWANGI SEBAGAI BAHAN AJAR SISWA - Mulyo, Robbi Nur; Sunardi, S; Monalisa, Lioni Anka; Setiawan, Toto Bara; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2018)
The purpose of this study was to explore ethnomatematics in citrus farmers’ activities to make teaching materials for students in the form of Students Worksheets (LKPD). The type of this studywas qualitative research with an ethnographic approach. Observation, interview, and documentation used as the data collection methods. The subjects of this study were three people in Pesanggaran Subdistrict. Ethnomatematics which was examined covering some activities such as calculate, measure, and design. This study focused on determining the areas, the amount estimation of trees based on planting distance, determining the amount of fertilizer based on trees and fertilizing period, and determining the incurred costs. The mathematical concepts that appeared in this study were operations, quadrilaterals, and proportion. Keywords: Ethnomathematics, Activities of Citrus Farmers, LKPD